John Ellis Jones and Ourania Kouka, Elis 1969. The Peneios Valley Rescue Excavation Project / Effie Photos-Jones and Alan J Hall, ros, mercator and the cultural landscape of Melos in antiquity - Bintliff, John (Journal of Greek Archaeology, 2021)
Both of these books represent much belated publications of older fieldwork. Appropriately perhaps, since we could not find suitable or willing reviewers, your Editor has undertaken to review these books, also considerably belatedly. But they remain little known and so well worth recognition. The Elis Survey was a British contribution to a rescue project shared out amongst several foreign archaeological schools in Athens, to document a landscape in Elis about to be drowned by a new dam and reservoir.